2021
DOI: 10.3390/microorganisms9102051
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Characterization of Fungal Biodiversity in Long-Term Polychlorinated Biphenyl-Contaminated Soils

Abstract: Polychlorinated biphenyls (PCBs) belong to the organic pollutants that are toxic to humans and harmful to environments. Numerous studies dealing with the impact of PCBs on soil microorganisms have focused on bacterial communities. The effects of PCBs on fungal communities in three different PCB-polluted soils from former industrial sites were investigated using high-throughput sequencing of the internal transcribed spacer 1 region. Significant differences in fungal alpha diversity were observed mainly due to s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…The studied site was heterogeneously contaminated by PCB indicating that pollution concentration was not location dependent. Literature reported other PCB polluted soils that presented heterogeneous pollution with PCB concentrations varying from 1 mg.kg -1 dry mass [45] to over than 800 mg.kg -1 dry 16 mass [25]. This ranked the Pont de Claix brownfield of this study as a "moderate" polluted site despite the weakly industrial painting production activity occurring in the past decades.…”
Section: Pcb Effect On Microbial Abundance and Activitymentioning
confidence: 71%
See 1 more Smart Citation
“…The studied site was heterogeneously contaminated by PCB indicating that pollution concentration was not location dependent. Literature reported other PCB polluted soils that presented heterogeneous pollution with PCB concentrations varying from 1 mg.kg -1 dry mass [45] to over than 800 mg.kg -1 dry 16 mass [25]. This ranked the Pont de Claix brownfield of this study as a "moderate" polluted site despite the weakly industrial painting production activity occurring in the past decades.…”
Section: Pcb Effect On Microbial Abundance and Activitymentioning
confidence: 71%
“…By using 454 pyrosequencing, more recent in situ studies identified Proteobacteria, Actinobacteria, Firmicutes and Basidiomycota phyla, including species already known to transform PCBs (Stella et al, 2017;Zenteno-Rojas et al, 2020). Other studies also reported that PCB contamination increased soil fungal richness and promoted the development of bacterial species able to metabolize these pollutants [24,25]. But among these studies focusing on microbial diversity under PCB contaminated ecosystems, none investigated micro-eukaryotes (other than Fungi) neither archaeal diversity.…”
Section: Introductionmentioning
confidence: 99%